Growing the next generation of trauma surgeon-scientists: Reflections on 20 years of research investment. Issue 3 (1st September 2022) - Callcut, Rachael A.; Dixon, Rachel; Smith, Jason W.; Zarzaur, Ben; ,
Abstract : Short term mentorship research engagements can yield significant academic productivity for promising young investigators. Abstract : INTRODUCTION: The Eastern Association for the Surgery of Trauma mission includes fostering research and providing career development opportunities. Eastern Association for the Surgery of Trauma has awarded for 20 years a research scholarship to a promising young investigator. The research mentorship efforts were expanded 5 years ago with the INVEST-C Hack-a-thon. INVEST-C provides an intensive, short-term engagement to propel junior faculty toward establishing research independence. This study investigates the impact of these programs on academic productivity. METHODS: Pubmed records, National Institutes of Health (NIH) Reporter data, and SCOPUS h-index were acquired for all scholarship (SCH) awardees from 2002 to 2021 (n = 20) and all INVEST-C (INV) participants (2017–2020, n = 19). Current type of practice, total number of funding awards, and timing of first award were ascertained. INVEST-C participants were also surveyed on an annual basis to track their progress. Medians (interquartile range [IQR]) are reported and compared (analysis of variance). RESULTS: Median publications (PUBs) of SCH awardees were 56 (IQR, 33–88), h-index was 16 (IQR, 12–21), and 25% of awardees have ≥1 NIH grant since their SCH. Among the last 10 awardees with a minimum of 2 years from SCH, 40% have received an NIH award compared with a mean NIH funding rate of 18.5% over the same period. For those remaining in academics (90% SCH), PUBs were higher for those >5 years (66 [IQR, 51–115]) versus <5 years from their SCH (33 [22–59]; p = 0.05), but there was no difference in h-index (16 [IQR, 14–25] vs. 15 [9–19], p = NS). Comparing the most recent 5 years of SCH to INV group, there was no difference in academic productivity as measured by total PUBs (SCH, 33 [IQR, 22–59] vs. INV, 34 [IQR, 18–44]; p = 0.7) or h-index (INV, 9 [IQR, 5–14]; p = 0.1). However, no attendee held research funding before INV, but 31.6% (6 of 19 attendees) have subsequently acquired ≥1 funding award (11 non-NIH, 1 NIH) in the short interval since participation. CONCLUSION: Investments in research activities have translated to significant extramural funding. Those in the last 5 years have been particularly fruitful with INV participants already achieving equal median academic productivity to SCH recipients. LEVEL OF EVIDENCE: Prognostic and Epidemiologic; Level III. Abstract :